A collaborative parent-teacher model for religious moderation education in early childhood in Indonesia - M. Suyuti Yusuf; Hadi Pajarianto; Baso Sulaiman (South African Journal of Childhood Education)
Background: Effective collaboration between parents and teachers is a crucial component of early childhood education (ECE) institutions in Indonesia. Both parties hold a fundamental responsibility for imparting knowledge within the formal school setting and the informal home environment.